Pengaruh Sales Growth, Debt to Equity Rasio (DER) dan Net Profit Margin (NPM) Terhadap Earning Per Share (EPS) pada Sub Sektor Minyak dan Gas - Ariadin, Septian M.; Rahmatia, Nafisah Nurul; Munandar, Aris (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine the effect of Sales Growth, Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on Earning Per Share (EPS) in oil and gas subsector companies listed on the Indonesia Stock Exchange. This study uses an associative research approach with a quantitative method. The population consists of oil and gas subsector companies listed on the Indonesia Stock Exchange, with a sample of four companies, namely PT Energi Mega Persada Tbk (ENRG), PT Perusahaan Gas Negara Tbk (PGAS), PT Medco Energi Internasional Tbk (MEDC), and PT AKR Corporindo Tbk (AKRA), during the 2021–2025 period. The sampling technique used was saturated sampling. The data were obtained from the companies' financial statements and analyzed using multiple linear regression with the assistance of SPSS. The results show that Sales Growth has a positive and significant effect on Earning Per Share (EPS), with a significance value of 0.024. Debt to Equity Ratio (DER) has a negative and significant effect on Earning Per Share (EPS), with a significance value of 0.014. Meanwhile, Net Profit Margin (NPM) has no significant effect on Earning Per Share (EPS), with a significance value of 0.262. Simultaneously, Sales Growth, Debt to Equity Ratio (DER), and Net Profit Margin (NPM) have a significant effect on Earning Per Share (EPS), with a significance value of 0.010. These findings indicate that sales growth and capital structure management are important factors to consider in improving Earning Per Share in oil and gas subsector companies